2014
DOI: 10.1152/jn.00485.2013
|View full text |Cite
|
Sign up to set email alerts
|

Tuning and spontaneous spike time synchrony share a common structure in macaque inferior temporal cortex

Abstract: Investigating the relationship between tuning and spike timing is necessary to understand how neuronal populations in anterior visual cortex process complex stimuli. Are tuning and spontaneous spike time synchrony linked by a common spatial structure (do some cells covary more strongly, even in the absence of visual stimulation?), and what is the object coding capability of this structure? Here, we recorded from spiking populations in macaque inferior temporal (IT) cortex under neurolept anesthesia. We report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 79 publications
(114 reference statements)
5
20
0
Order By: Relevance
“…Together with our previous report (Lin et al, 2014 ), these tests provide additional support for the hypothesis that correlated activity supports efficient processing and behavior. We report that although the concepts of sparseness and decorrelation are often conflated, correlation strength and sparseness (when measured as tuning sharpness) should be considered as separate factors.…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…Together with our previous report (Lin et al, 2014 ), these tests provide additional support for the hypothesis that correlated activity supports efficient processing and behavior. We report that although the concepts of sparseness and decorrelation are often conflated, correlation strength and sparseness (when measured as tuning sharpness) should be considered as separate factors.…”
Section: Introductionsupporting
confidence: 87%
“…Second, the dense multi-depth arrays allowed us to examine layer specificity, which can tell us about input-output relationships. We and others (Sato et al, 2009 ; Lin et al, 2014 ; Tamura et al, 2014 ) previously reported that local IT populations have a correlational structure in which most neurons are weakly correlated and few neurons have strong tuning correlation and significant spontaneous coincident spiking (~6% of neuronal pairs in IT, vs. ~50% of pairs in V1; Chu et al, 2014 ). Yet, these rare IT choristers are also highly efficient.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In contrast, H corr has the potential to estimate neuronal selectivity across brain regions from a single data set, including resting state scans. More specifically, because previous single unit recording studies (Bair et al, 2001; Jermakowicz et al, 2009; Lin et al, 2014) found that pair-wise correlations between two neurons in the presence of visual stimuli can be detected in the absence of stimuli, thus the voxel-wise correlations and H corr within a given region should be similar with or without a task. Similar neural mechanisms might also underlie the findings from fMRI studies of resting state (Fox and Raichle, 2007; Smith et al, 2009).…”
Section: Discussionmentioning
confidence: 99%